Telomerase Reverse Transcriptase (TERT) Regulation in Thyroid Cancer: A Review - McKelvey, Brittany A.; Umbricht, Christopher B.; Zeiger, Martha A. (Frontiers in Endocrinology, 2020)
Telomerase reverse transcriptase (TERT) is the catalytic subunit of the enzyme telomerase and is essential for telomerase activity. Upregulation of TERT expression and resulting telomerase activity occurs in the large majority of malignancies, including thyroid cancer. This upregulation results in continued cellular proliferation and avoidance of cellular senescence and cell death. In this review we will briefly introduce TERT and telomerase activity as it pertains to thyroid cancer and, highlight the effects of TERT on cancer cells. We will also explore in detail the different TERT regulatory strategies and how TERT is reactivated in thyroid cancer cells, specifically. These regulatory mechanisms include both activating single base pair TERT promoter mutations and epigenetic changes at the promoter, including changes in CpG methylation and histone modifications that affect chromatin structure. Further, regulation includes the allele-specific regulation of the TERT promoter in thyroid cancer cells harboring the TERT promoter mutation. These entail allele-specific transcriptional activator binding, DNA methylation, histone modifications, and mono-allelic expression of TERT. Lastly, TERT copy number alterations and alternative splicing are also implicated. Both amplifications of the TERT locus and increased full-length transcripts and decreased inactive and dominant negative isoforms result in active telomerase. Finally, the clinical significance of TERT in thyroid cancer is also reviewed.